A31: Vitamin D Status is a Determinant of the Effect of Atorvastatin on Carotid Intima Medial Thickening Progression Rate in Children with Lupus: An Atherosclerosis Prevention in Pediatric Lupus Erythematosus Substudy. Issue 11 (March 2014) - Robinson, Angela; Tangpricha, Vin; Yow, Eric; Gurion, Reut; Schanberg, Laura E.; McComsey, Grace; ,
Abstract : Background/Purpose: Epidemiologic associations suggest that vitamin D status may play a role in inflammation and progression of atherosclerosis. Using frozen serum, carotid intima medial thickness (CIMT) measurements, and other existing data from the Atherosclerosis Prevention in Pediatric Lupus Erythematosus (APPLE) trial, we assessed interactions between serum 25‐hydroxyvitamin D [25(OH)D], atorvastatin randomization, and CIMT progression rate. Methods: Participants in the 3‐year APPLE trial were randomized to placebo or atorvastatin and CIMT progression rate was measured. Frozen serum collected at baseline was used to measure 25(OH)D levels by chemiluminescent assay (IDS, LTD). Mixed effect longitudinal models for the outcome CIMT progression at 3 years were used to evaluate interaction between vitamin D deficiency [25(OH)D levels <20 ng/mL] at baseline and atorvastatin or placebo treatment, and adjusted for lupus duration, gender, systolic blood pressure, pubertal level, LDL‐cholesterol, and the log of baseline high sensitivity C‐reactive protein. Results: 201/221 APPLE participants had available samples and were included in this analysis; 61/201 (30%) had vitamin D deficiency at baseline. In univariable linear regression modeling, baseline vitamin D deficiency was associated with increased baseline mean‐max IMT (p = 0.01). In multivariable longitudinal modeling, there was a significant interaction effect between baseline vitamin D deficiency and atorvastatin treatment in 3‐year progression of mean‐max CIMT (see Figure). In 4 out of 6 carotid segments, there was a greater decrease in mean‐max CIMT progression rate in subjects who were treated with atorvastatin compared to placebo if they had baseline 25(OH)D levels ≥20ng/mL. Conclusion: Subjects with higher serum 25(OH)D (≥ 20ng/mL) had lower mean‐max CIMT progression following 3 years of atorvastatin treatment. Results from secondary analyses must be interpreted cautiously, but these findings suggest that treating underlying vitamin D deficiency may optimize benefits from statin therapy.